Trends in Mathematics Research in Early Childhood: Bibliometric Review - Swasti Maharani (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood education is a critical stage in individual development. At an early age, children have the ability to absorb knowledge quickly, including in mathematics. The aim of this study was to identify trends and patterns of mathematics research in early childhood using bibliometric analysis. The data was obtained from the Scopus database which has been refined with 4 stages (identification, screening, eligibility, and inclusion). The results showed that the peak of publications related to mathematics research in early childhood occurred in 2022. 2017 was the year with the most influential publications. Journal “Early Childhood Education Indexed Journal Scopus with the highest quartile score (Q1) is the most popular place for publication of previous research related to this field. The United States is the most influential country in this field because both the number of publications and the number of citations are the highest than any other country. As for three focus study related study mathematics in children age early on the Scopus database from 1988-2023 namely, 1) mathematics, human, learning and gender; 2) early childhood, professional development, and teachers; 3) mathematics learning, early childhood, curriculum, and achievement.